MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN DISIPLIN SANTRI - Erles (UNISAN JURNAL, 2024)
Discipline is obedience to respect and implement a system that requires people to submit to applicable decisions, orders and regulations. The aim of this research is to analyze Islamic Education Management in Improving Student Discipline at Madrasah Diniyah Takmiliyah Awaliyah At Thaha Kuantan Singingi. The author in this research uses a method that focuses more on the use of an approach model that focuses on the content of the study or content analysis. Discussion and data collection by the author was carried out through various media, both print and electronic, such as books, e-books, scientific journals, and so on. The results of this research are (1) Islamic education planning in forming student discipline: planning of discipline carried out by stakeholders and socialized to students. (2) Organizing Islamic education in forming student discipline, the head of the madrasah appoints several teachers or staff who are given additional duties to organize and be responsible for the smooth running of planned disciplinary activities so that they run well. (3) The implementation of Islamic education in forming this discipline includes all parties, all madrasa stakeholders, especially the object, namely students. (4) Supervision of Islamic education in forming student discipline at Madrasah Diniyah Takmiliyah Awaliyah At Thaha by the head of the madrasah and guardians. Keywords: Islamic Education Management, Increasing Discipline